Ecoprint Totebag sebagai Sarana Literasi Ekonomi dan Kreativitas Bagi Anak-Anak Desa Sempajaya - Diah Safithri Armin; Ummi Azhany Husna Nasution; Yessy Agustia Lestari; Dermilan Siregar (Pusat Riset dan Inovasi Nasional, 2026)
The 2025 UINSU Community Service Program research in Sempajaya Village was carried out through training in making ecoprint tote bags as an effort to develop creativity while strengthening the economic literacy of elementary school children. This activity utilized natural materials such as leaves and flowers commonly found in the village environment, so that children could learn to recognize the potential of their natural surroundings as a source of creative works with practical and economic value. The training was conducted in three main stages: preparation, implementation, and reflection. During the implementation stage, children were introduced to the concept of ecoprinting, pounding techniques, and the steps involved in making ecoprinted tote bags through lectures, question and answer sessions, and hands-on practice. The results of the activity showed an increase in the participants' creativity, as evident in their ability to arrange motifs, select natural materials, and produce tote bags with attractive patterns. In addition, this activity also fostered a basic understanding of the economic value of creative products, thereby supporting the formation of independence and an entrepreneurial spirit from an early age. The reflection stage showed that the children were able to identify the process, benefits, and challenges they faced. Thus, ecoprint tote bags proved to be an effective educational tool in integrating creativity, economic literacy, and love for the environment for the children of Sempajaya Village.